Experimental and numerical investigation of impact resistance in mixed steel fiber-reinforced concrete: Synergistic effects of short and long fibers with simulation validation - Vikrant S Vairagade; Shrikrishna A Dhale; Pranita Bhandari; Sagar Shelare; Shubham Sharma; Manish Sharma; Ankur Kulshreshta; Dražan Kozak; Mohamed Abbas; Jasmina Lozanovic (Journal of Engineered Fibers and Fabrics)
This study has compared numerical simulations of plain concrete (PC) and mixed steel fiber-reinforced concrete (MSFRC) impact loading results with experimental findings regarding blows needed and impact energy at first crack and ultimate failure. These experimental testing findings were based on a testing protocol that was recommended by ACI committee 544. Hooked end steel fibers of 25 and 50 mm length with 1 mm constant diameter at various volume fraction were combine systematically to get synergistic effect. The findings of an experimental and the computational analyses suggested that raising fiber volume fraction increased an impact resistance of concrete significantly. The numerical simulation replicated experimental data, suggesting that a numerical technique may accurately predict test findings.